Building Digital Trust: The Role of Trust in the Relationship Between User-Generated Content (UGC), E-WOM, and Purchase Intention Among Generation Z - Achmad Junaidi; Yoga Nindhita (Universitas Negeri Semarang, 2025)
This study investigates the impact of User-Generated Content (UGC), Electronic Word of Mouth (e-WOM), and trust on Generation Z’s purchase intention toward Facetology sunscreen products in the context of rapid digital transformation and the growing influence of social media on consumer behavior. As consumers increasingly rely on peer-generated information rather than traditional corporate advertising, the study extends the Theory of Reasoned Action to explain the relationship between digital information, trust, and purchase intention. The research adopts a quantitative approach using Partial Least Squares (PLS) analysis with SmartPLS 4.0 software. The findings demonstrate that both UGC and e-WOM positively influence purchase intention, while trust functions as a mediating variable that strengthens this relationship. In addition, trust also acts as a moderating variable by amplifying or weakening the effects of UGC and e-WOM on purchase intention. The results indicate that when consumers have a high level of trust in a product or brand, the positive influence of favorable reviews and peer recommendations becomes stronger in encouraging purchase intention. Conversely, when trust is low, the positive impact of UGC and e-WOM tends to weaken and may even become negative.